2020
DOI: 10.53936/afjare.2020.15(4).21
|View full text |Cite
|
Sign up to set email alerts
|

Income and greenhouse gas (GHG) emission trade-offs on smallholder farms at two sites in northern Nigeria

Abstract: This study analyses the trade-offs between welfare (measured by income) and greenhouse gas (GHG) emissions using a farm-level optimisation model that incorporates the predominant cereal (sorghum), legumes (groundnut, soybeans), livestock (cattle, goats and sheep) and trees (locust bean, camel’s foot) representative of production systems at two contrasting sites in northern Nigeria. The optimisation model maximises the value of total farm production, subject to constraints on GHG reductions of 10%, 25% and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous research (Ayinde et al, 2020) examined the farm-level impacts of restrictions on GHG emissions for two types of farms in Northern Nigeria using a farm-level optimization model. In analyses for a single year (2015), we found that limits on GHG emissions would reduce farm household income and modify production patterns, land use and input purchases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research (Ayinde et al, 2020) examined the farm-level impacts of restrictions on GHG emissions for two types of farms in Northern Nigeria using a farm-level optimization model. In analyses for a single year (2015), we found that limits on GHG emissions would reduce farm household income and modify production patterns, land use and input purchases.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this paper is to assess the impacts of inter-annual variation in input costs, input use, output prices and product yields on the trade-offs between farm income and GHG emissions. Similar to Ayinde et al, (2020) we analyse these trade-offs for two production systems in Nigeria that incorporate trees, grain and legume crops, and multiple livestock species. We compare the impacts of GHG restrictions for ve production cycles from 2015/16 to 2019/2020.…”
Section: Introductionmentioning
confidence: 99%